Family Composition of Inhabitants from Šiauliai City and County at the End of the 18th Century - Giedrimas, Laurynas (Acta humanitarica academiae Saulensis, 2025)
The article presents a comparative analysis of the structure of the families of the nobles, free people and peasants living in the towns of Šiauliai and Žagarė, as well as the small towns of Šiauliai county, which aims to answer the question of how much the family structure of the residents of the county center Šiauliai differed from other cities and towns in the county, so as well as families of village residents. In addition, the aim is to find out whether at the end of the 18th century, there was an “urban” family model. Using Eugene Alfred Hammel ir Peter Laslett’s (1974) typology, established in historical demography, families are classified into solitary, non-family, nuclear, extended and multiple families, paying attention to the proportion of single and nuclear families. In the analysis, families are divided not only by class, but also into those with and without immovable property. Empirical analysis shows that among residents with and without immovable property, the largest number of nuclear families was among the residents of the cities of Šiauliai and Žagarė. Meanwhile, among the freedmen and peasants who owned the immovable property, although nuclear families made up a significant proportion, there was no single dominant family model. However, landless free people and peasants mostly lived only in nuclear families. On the other hand, solitaries were more common among Šiauliai and Žagarė residents who did not have immovable property than among rural residents. The results of the study suggest that non-agricultural activities and lack of immovable property encouraged living in nuclear families, but this family model did not necessarily depend on whether the family lived in the city or the countryside.